African ark : mammals, landscape and the ecology of a continent - Monadjem, Ara; Unwin, Mike (Wits University Press, 2023)
African Ark tells the story of how Africa's mammals have helped shape the continent's landscapes over time to support an amazing diversity of life. It explores the impact of megafauna on the environment, also highlighting small mammals such as rodents and bats, and their interaction with the people who live alongside them.